A educação física na educação infantil a partir da ótica de gestores municipais - Eliane Aparecida Nogueira; Eduard A Bendrath; Andreia Paula Basei (Universidade Federal de Rondônia, 2018)
Physical Education in early childhood education has a fundamental role in the process of human development since it provides the knowledge of the subject and his world from the movement. The objective of this study was to analyze under the prism of educational management and legal instruments, the integration of physical education as a component of early childhood education from the point of view of two public managers of municipalities in Paraná. The data collected through semi-structured interviews were analyzed through content analysis, being created categories in posteriori. It was noted that from the point of view of management, physical education has relevance declared, but their inclusion is placed in the background because of administrative priorities managerial.